Influence of biochemical treatments on consortium of rhizobacteria and soil fertility - Umer, Muhammad; Shabbir, Saba; Chaudhary, Neelam; Hussain, Qaiser; Abbas, Shabbar; Afzal, Muhammad Inam; Sajjad, Muhammad (Bangladesh Journal of Botany, 2020)
Soil was treated with different biochemicals i.e. NPK, compost, biochar, humic acid and their combination. New approach was designed to assess the impact of applied biochemicals on the activities of whole bacterial community in spite of pure isolates. The results showed that these biochemically mediated plant beneficial bacteria taken together efficiently solubilized the tri-calcium phosphate, when supplemented in Pikovskaya's broth (PKV). Phosphorus solubilization ranged from 0.231 to 0.605 μg/ml. The isolated consortium of rhizobacteria was positive for IAA production both with LB only and LB + tryptophan medium. The amount of IAA was increased by 0.25 - 1.5 folds with the addition of tryptophan to LB medium. These biochemical treatments were further tested for their effects on soil fertility improvement. Soil available phosphorus was found to improve significantly available phosphorus which ranged from 6.33 to 8.733 mg/kg. Soil pH, moisture content and organic matter were found to increase remarkably by the application of these treatments.